2019
DOI: 10.3892/mco.2019.1953
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the optimal cetuximab concentration that is effective against oral squamous cell carcinoma in collagen gel droplet embedded culture drug sensitivity testing

Abstract: Anticancer drug sensitivity testing using the collagen gel droplet embedded culture drug sensitivity test (CD-DST) on oral squamous cell carcinoma (OSCC) samples beginning from 2010 has been conducted. The present study investigated the effect of adding cetuximab (Erbitux ® ), a molecularly targeted drug, on anticancer drug activity against clinical OSCC specimens. A total of 25 specimens were obtained from 25 patients with OSCC between October 2013 and December 2017. The present study conducted anticancer dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Similarly, as previously reported, sensitivity tests using cisplatin, fluorouracil, or docetaxel for OSCC showed a success rate of 81.8% in primary cultures, with a clinical predictive value of 92.8% [14]. In addition, anticancer drug susceptibility tests, including those of cetuximab-associated samples from patients with OSCC, were performed with success rates of 83.3% for primary tumors, 100% for metastatic lymph nodes, and 84.0% overall [15]. Therefore, the CD-DST can be used to determine the susceptibility of OSCC to various types of anticancer drugs combined with cMab.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similarly, as previously reported, sensitivity tests using cisplatin, fluorouracil, or docetaxel for OSCC showed a success rate of 81.8% in primary cultures, with a clinical predictive value of 92.8% [14]. In addition, anticancer drug susceptibility tests, including those of cetuximab-associated samples from patients with OSCC, were performed with success rates of 83.3% for primary tumors, 100% for metastatic lymph nodes, and 84.0% overall [15]. Therefore, the CD-DST can be used to determine the susceptibility of OSCC to various types of anticancer drugs combined with cMab.…”
Section: Discussionsupporting
confidence: 73%
“…Ryuki et al [21] reported that the results of contact with cisplatin and fluorouracil with additional cMab were consistent between the CD-DST and nude mice method using a clinically equivalent dose that reproduced human serum concentration [21]. Furthermore, Sakuma et al [15] reported that clinical efficacy can be predicted using clinical specimens obtained from biopsy. Therefore, the CD-DST can be used to evaluate the contact of PTX alone and in combination with cMab, which is useful for predicting clinical antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method has advantages in that it allows testing using smaller quantities of cells compared with conventional assays. Furthermore, it eliminates the effects of fibroblasts that can adulterate samples at the time of harvesting and allows the evaluation of physiological drug concentrations [13][14][15][16] . In addition, the CD-DST method can be evaluated by combining multiple anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, as previously reported, sensitivity tests using cisplatin, fluorouracil, or docetaxel at OSCC showed a success rate of 81.8% in primary culture 15) . In addition, we conducted anticancer drug susceptibility tests, including those for cetuximab, using OSCC samples with success rates of 83.3% for primary tumors, 100% for metastatic lymph nodes, and 84.0% overall 16) .…”
Section: Introductionmentioning
confidence: 99%